Human sweat-based wearable glucose sensor on cotton fabric for real-time monitoring - Anoop Singh; Asha Sharma; Sandeep Arya (Journal of Analytical Science and Technology, 2022)
Abstract In this work, a human sweat-based wearable sensor for real-time glucose monitoring has been fabricated on a cotton substrate after treating it with a two-step polymerization of pyrrole. The pyrrole-treated fabric was coated with solution of copper sulphate pentahydrate to grow Cu layer. The cotton/pyrrole/Cu fabric was treated with the solutions of copper acetate and manganese acetate to form Cu–Mn transition-metal alloy via electrochemical deposition technique. Results indicate that the developed sensor is reliable with glucose detection limit of 125 µM and 378 µM. In addition, the sensor output ranged between 50 and 400 µM glucose with coefficient of correlation, R 2 = 0.983, indicating a linear range of output current. The sensor's response is not significantly affected by interferents. The developed sensor is also validated on human sweat with satisfactory results.